Empowering Elderly Women through Education: Optimizing Traditional Leather Puppet Shows and Hadrah as a Creative Learning Medium - Sidik Jatmika; Ajeng Puspa Marlinda; Muhammad Alfi; Muhammad Indrawan Jatmika (Journal of Social and Community Development, 2025)
This paper explores the innovative educational efforts undertaken by ‘Aisyiyah, the women’s wing of Muhammadiyah, to empower elderly women through special educational programs. ‘Aisiyah use traditional leather puppet shows (Wayang Kulit) and Hadrah Music as an innovative and culturally relevant medium to educate elderly women. By integrating local wisdom and interactive performance art, the project aims to enhance lifelong learning, health awareness, and social inclusion among older women. The findings affirm that education, even later in life, can be a powerful tool for dignity, empowerment, and intergenerational solidarity. The optimization of Wayang Kulit and Hadrah in this context not only preserves intangible cultural heritage but also serves as a powerful tool for participatory education, promoting active aging and community engagement.